Assessing historical climate trends in Dhaka City: A multivariate analysis using Mann-Kendall and Sen’s slope method - Hossen, Md Sabbir; Evan, Raian Islam (International Journal of Climate Research, 2023)
This study presents a comprehensive assessment of the historical climatology of Dhaka city over a period of fifty years (1971-2021), utilizing five distinct climate parameters: Skin Temperature, Air Temperature, Rainfall, Wind Speed, and Humidity. The study employed various statistical methods, such as Linear regression, the Mann-Kendall test model, and Sen’s slope estimator method, to examine the significant patterns in climate data and quantify the degree of fluctuations in the variables. The results of the Mann-Kendall Test provided evidence that each parameter’s values displayed a statistically significant trend. The Sen’s Slope estimator revealed a declining trend in the monthly mean value of all climate parameters except for wind speed and humidity. The annual average Skin and Air Temperature in Dhaka City increased at a rate of 0.033°C and 0.065°C respectively over the study period; as a result, the average annual Rainfall and Humidity showed an increasing tendency, which was 1.225 mm and 0.086% respectively. The Monsoon period demonstrated the highest rainfall and humidity levels, while the winter season demonstrated the lowest levels of these parameters. The trend of Wind Speed has exhibited a decrease at a rate of 0.032 m/s over the past five decades. A critical analysis evaluates the trends and patterns observed in the data. This research attempts to improve understanding of the components that have influenced the climate of Dhaka City by evaluating historical data.